2015
DOI: 10.6113/jpe.2015.15.6.1438
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Implementation of a DC-DC Converter for Hybrid Power Supplies Systems

Abstract: A new DC-DC power converter is researched for renewable energy and battery hybrid power supplies systems in this paper. At the charging mode, a renewable energy source provides energy to charge a battery via the proposed converter. The operating principle of the proposed converter is the same as the conventional DC-DC buck converter. At the discharging mode, the battery releases its energy to the DC bus via the proposed converter. The proposed converter is a non-isolated high step-up DC-DC converter. The coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Figs. 6 and 7 illustrate that the secondary output voltages satisfy formula (7). Moreover, the simulated and experimental results are consistent with the theoretical conclusions given in Section 2.…”
Section: Cross-regulation Analysis Of Fly-buck Convertersupporting
confidence: 84%
See 1 more Smart Citation
“…Figs. 6 and 7 illustrate that the secondary output voltages satisfy formula (7). Moreover, the simulated and experimental results are consistent with the theoretical conclusions given in Section 2.…”
Section: Cross-regulation Analysis Of Fly-buck Convertersupporting
confidence: 84%
“…The single-input and multiple-output (SIMO) dc-dc converters are commonly utilised in different kinds of applications including factory automation, stand-by power suppliers, and so on. SIMO dc-dc converters have been widely discussed [1][2][3][4][5][6][7][8]. Research has shown that cross-regulation is the most critical issue in SIMO converters [9].…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [16] use coupled inductor, a DC-DC converter, to charge the battery from input source and increase voltage and supply load from the battery. This converter provides high-voltage gain but it cannot directly transfer power from the input source to the load.…”
Section: Introductionmentioning
confidence: 99%
“…In [4], coupled inductors were employed to achieve a high voltage gain; however, the main and auxiliary switches operate under hard switching conditions, leading to higher switching losses and lower efficiency. A step-up converter proposed in [17] utilizes a snubber circuit comprising coupled inductors; this structure results in a ripple-free output current, but both switches are turned off under hard switching conditions.…”
Section: Introductionmentioning
confidence: 99%